Working Capital Management – a Comparative Study of Hcl Info System Limited and Zenith Computer Limited: A Comparative Analysis of Working Capital Management and Bank Credit Relationship (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Working capitalmanagement is an important aspect in firm’s financial management decision. Anoptimal working capital management is expected to contribute positively to thecreation of the firm value. To reach optimal working capital management firmmanager should control the tradeoff between profitability and liquidityjudiciously. Main purpose of this study is to measure the liquidity position ofthe two major computers companies and relationship between working capital andbank credit to know managerial efficiency of working capital. For analyzing thedata, ratio analysis and various statistical tools and techniques were used.The data for analysis covering the period (2008-2012) is collected from thefinancial statements published in the annual reports. It was found that theposition of working capital management of both the companies is very sound. Itis also found that there is significant positive relationship between workingcapital and bank credit in case of HCL Info system Ltd. whereas it is foundinsignificant in case of Zenith Computers at the 5% level of significance.